Discovery of papyifuran A as an unusual cembrane diterpenoid from Boswellia papyrifera resin reveals EEF2 as a potent new drug target for fibrosis of multiple organs - Madhu Babu Sura; Yeting Zhou; Jijun Li; Yongxian Cheng (Acta Pharmaceutica Sinica B)
Chronic kidney disease (CKD) affects 8%–15% of the population globally and can cause renal failure, partly due to lack of effective treatments and drug targets. Three novel cembrane diterpenoids papyifurans A‒C (1–3), in particular of 1 with an unprecedented trioxatetracyclo[10.2.1.12,5.16,9]heptadecane polyether scaffold, derived from Boswellia papyrifera resin, were found to effectively protect against renal fibrosis in vitro and in vivo. Their structures were fully characterized using a combination of spectroscopic, computational, modified Mosher’s, and X-ray crystallographic analysis. In particular, we performed chemical proteomic analyses and found that Elongation factor 2 (EEF2) is the key target of compound 1 for anti-renal fibrosis in vitro. Moreover, previous studies have linked EEF2 with lung fibrosis, while compound 1 was found to inhibit the hallmarks of organ fibrosis in vitro. Such effects were observed to decrease with the knock down of EEF2 in vitro, suggesting that EEF2 might be a universal drug target of organ fibrosis. Collectively, the present study demonstrated an example of identifying drug targets by using structurally novel natural products, which will be beneficial for developing therapeutic agents against organ fibrosis.